The Nasher Collection : A Century of Sculpture - Brenson, Michael; Gimenez, Carmen; Krens III, Thomas; Nash, Steven A.; Nasher, Raymond; Parker, Harry S.; Fine Arts Museums of San Francisco (New York : The Solomon R. Guggenheim Foundation, 1996)
Abakanowicz, Magdalena ; Andre, Carl ; Archipenko, Alexander ; Arp, Hans (Jean) ; Borofsky, Jonathan ; Brancusi, Constantin ; Braque, Georges ; Burton, Scott ; Calder, Alexander ; Caro, Anthony ; Chamberlain, John ; Cragg, Tony (Anthony) ; Deacon, Richard ; Dubuffet, Jean ; Duchamp-Villon, Raymond ; Ernst, Max ; Flanagan, Barry ; Gabo, Naum ; Gaudier-Brzeska, Henri ; Gauguin, Paul ; Giacometti, Alberto ; González, Julio ; Gormley, Antony ; Hepworth, Barbara ; Judd, Donald ; Kapoor, Anish ; Kelly, Ellsworth ; Kirili, Alain ; Koons, Jeff ; Lachaise, Gaston ; Laurens, Henri ; Lichtenstein, Roy ; Lipchitz, Jacques ; Long, Richard ; Maillol, Aristide ; Matisse, Henri ; Miro, Joan ; Moore, Henry ; Newman, Barnett ; Noguchi, Isamu ; Oldenburg, Claes ; Pevsner, Antoine ; Picasso, Pablo ; Puni, Ivan ; Puryear, Martin ; Rodin, Auguste ; Rosso, Medardo ; Rückriem, Ulrich ; Segal, George ; Serra, Richard ; Shapiro, Joel ; Smith, David ; Smith, Tony ; Stores, John ; Suvero, Mark di ; Tucker, William ; Wilmarth, Christopher ; de Kooning, Willem
biografie
The Nasher Collection : A Century of Sculpture, Fine Arts Museum of San francisco, California Palace of the Legion of Honor, October 1996 - January 1997 ; The Solomon R. Guggenheim Foundation, New York, February - April 1997
Engels
boek